2017
DOI: 10.1038/s41598-017-08388-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Hypobaric Hypoxia Improves Cardiac Function through Inhibition of Endoplasmic Reticulum Stress

Abstract: We investigated the role of endoplasmic reticulum stress (ERS) in chronic intermittent hypobaric hypoxia (CIHH)-induced cardiac protection. Adult male Sprague-Dawley rats were exposed to CIHH treatment simulating 5000 m altitude for 28 days, 6 hours per day. The heart was isolated and perfused with Langendorff apparatus and subjected to 30-min ischemia followed by 60-min reperfusion. Cardiac function, infarct size, and lactate dehydrogenase (LDH) activity were assessed. Expression of ERS molecular chaperones (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Viability was determined by the level of formazan using a spectrophotometer at 550 nm. Based on previous studies from our own and other labs [21, 2831], cardiac LDH release at 5 min of reperfusion in the coronary effluent was determined by spectrophotometry following the commercial kit manual. After reperfusion for 120 min, the myocardial MDA level was determined by spectrophotometry according to the commercial kit manual [21, 28].…”
Section: Methodsmentioning
confidence: 99%
“…Viability was determined by the level of formazan using a spectrophotometer at 550 nm. Based on previous studies from our own and other labs [21, 2831], cardiac LDH release at 5 min of reperfusion in the coronary effluent was determined by spectrophotometry following the commercial kit manual. After reperfusion for 120 min, the myocardial MDA level was determined by spectrophotometry according to the commercial kit manual [21, 28].…”
Section: Methodsmentioning
confidence: 99%
“…The authors suggested that the mechanism of PTSD-induced myocardial damage involved endoplasmic reticulum stress. Yuan et al [37] reported that IHC prevented cardiac dysfunction and apoptosis by suppressing endoplasmic reticulum stress in ischemic myocardium. Data obtained by Wang and Si [38] showed that IHC protected myocardium from reperfusion injury by inhibiting myocardial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were randomly divided into CIHH treatment (CIHH) and control groups after bone fracture surgery. As previously described ( 33 , 34 ), the rats in the CIHH group were exposed to a hypobaric hypoxia chamber (Pressure: 50 kPa, oxygen concentration: 10%-11%, 22°C ± 1°C) for 6 continuous hours (from 10:100 to 16:00) every day, and the rest time was kept in normal conditions. The control rats were housed under normal conditions.…”
Section: Methodsmentioning
confidence: 99%